The Wiley Handbook of Violence and Aggression 2017
DOI: 10.1002/9781119057574.whbva022
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Genetic and Environmental Influences on the Development of Aggressive–Antisocial Behavior during Childhood and Adolescence

Abstract: For both perpetrators and their victims, aggressive–antisocial behavior during childhood and adolescence is related to concurrent and later adjustment problems, including violent and criminal behavior. Quantitative (i.e., behavioral) genetic studies have shown that aggressive–antisocial behavior, as well as related risk factors such as negative parenting, are subject to both genetic and environmental influences. In this chapter, we present evidence from genetically informed studies regarding the additive and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Results clearly showed that children's use of aggression can be influenced through their close friendships, even when genetic effects are controlled. However, in a follow‐up study of the same MZ twins from middle childhood to early adolescence, no effect of best friends’ aggression was found (Vitaro et al., ), possibly because older children increasingly select their social environment in tune with their genetic dispositions (Vitaro, Brendgen, & Tremblay, ).…”
Section: Genetic Effectsmentioning
confidence: 99%
“…Results clearly showed that children's use of aggression can be influenced through their close friendships, even when genetic effects are controlled. However, in a follow‐up study of the same MZ twins from middle childhood to early adolescence, no effect of best friends’ aggression was found (Vitaro et al., ), possibly because older children increasingly select their social environment in tune with their genetic dispositions (Vitaro, Brendgen, & Tremblay, ).…”
Section: Genetic Effectsmentioning
confidence: 99%
“…The first aim of the current study was to examine trajectories of relational and physical aggression across early childhood. Researchers have found that physical aggression typically peaks in toddlerhood (i.e., 18-30 months) and then decreases across early childhood (Tremblay, 2000;Vitaro & Brendgen, 2011). Relational aggression is first observable at around 30 months of age (Crick et al, 2006) and becomes more prevalent in middle childhood with a peak in early adolescence (Fite & Pederson, 2018).…”
Section: Trajectories Of Aggressive Behavior In Early Childhoodmentioning
confidence: 99%
“…Relational aggression has been reliably observed around 30 months, and a wealth of research has examined relational aggression during early childhood (e.g., 106 articles examined relational aggression for children 0-8 years of age; for a review, see Swit & Slater, 2021). Relational aggression has been theorized to increase as children get older, and peaks in early adolescence (Crick et al, 2006;Fite & Pederson, 2018) and physical aggression peaks in toddlerhood, is common in preschool, and substantially decreases by middle childhood (Tremblay, 2000;Vitaro & Brendgen, 2011). Children who demonstrate higher levels of aggressive behavior as they leave preschool are at a risk for a number of negative outcomes, such as peer, academic, and psychological difficulties (Early Child Care Research Network, 2004).…”
mentioning
confidence: 99%